Copper and Lead Contamination in Sediment and Benthic Ecosystems of Sembilang National Park’s Coastal Region, South Sumatra - Rozirwan; Ananta, Dio Alif; Khotimah, Nadila Nur; Putri, Wike Ayu Eka; Fauziyah; Dianysah, Gusti; Siregar, Yusni Ikhwan; Ramses; Isnaini; Melki; Aryawati, Riris; Agustriani, Fitri; Nugroho, Redho Yoga (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Littoral zone often face environmental pressure due to anthropogenic activities, which can impact the quality of their ecosystem. This study analyzes the concentrations of copper (Cu) and lead (Pb) in sediments and benthic (Anadara granosa and Cerithidea cingulata). Sampling procedures were implemented during September 2022 across the aquatic habitats of Sembilang National Park, in South Sumatra Province, using the purposive sampling method. Sediment grain size and substrate type were analyzed using Shepard’s triangle. Metal detection using a spectrophotometric method based on atomic absorption. The results showed that the sediment fraction mostly consisted of clay, ranging from 92.03% to 94%. Cu concentrations in the sediment ranged from 5.01±0.017 to 5.71±0 mg/kg, while Pb concentrations ranged from 10.5±0.195 to 11.51±0.395 mg/kg. In the benthic, Cu concentrations ranged from 0.0037±0.00005773 to 0.0147±0.00000346 mg/kg, and Pb concentrations ranged from 0.0001±0.000227 to 0.005±0 mg/kg. According to the statistical evaluation testing via independent sample t-test showed that heavy metals differed significantly (p <0.05) between sediment and benthic compartments. These results show that the environmental quality in Sembilang National Park is still comparatively well maintained and within current quality requirements, despite certain activities that have the potential to pollute the environment. To guarantee the long-term viability of this area, it is advised that environmental quality be frequently monitored as a mitigation action.